Perceptions of healthcare providers in Manila towards immunizing pharmacists - Co, Helena Selene T.; Conde, Anlorenze Mae B.
Immunization is a key element in the prevention of infectious disease. However, some vaccine preventable diseases, such as influenza and pneumonia are still among the top ten causes of morbidity. This may be reflective of the underutilization of vaccines. An approach for improving delivery of immunizations is to increase the number of sites where patients obtain immunizations, such as community pharmacy. In the country, the Philippine Pharmacists Association and the Food and Drug Administration and Department of Health, have engaged in training community pharmacists to administer adult vaccines. A perceived major barrier to the implementation of pharmaceutical care in healthcare settings is the lack of support from other health professionals. This study aimed to describe the perceptions of healthcare providers towards pharmacists as immunizers in Manila, and to identify factors that affect their level of acceptance towards this extension of the pharmacist's role, through the use of a self-administered questionnaire. Through quota sampling, a total of 82 nurses (45.8%) and 32 family practice physicians and general practitioners (17.9%) were surveyed. Majority of the respondents were female (52.6%), working in a public institution (76.3%) and aged less than 30 years old (68.4%). Results showed that most of the respondents agreed on the items regarding the competence of the pharmacist to immunize (mean = 3.21 + 0.68) and on the increased accessibility of vaccinations to the community (mean=3.12 + 0.83). Although most respondents also believed that their professional services will be negatively affected by the extension of the pharmacists' roles, this is in a lesser magnitude compared to the other two variables (mean = 2.54 + 0.51). Overall, majority of the health care providers (79.81% supported the extended role of an immunizing pharmacist (mean = 3.10 + 0.80). Statistical analysis showed that profession (P=0.0127) and both competence and accessibility (P<0.0127) and both competence and accessibility (P<0.001) are significant predictors of the level of acceptance. However, the surveyed healthcare providers may not be representative of all physicians and nurses in the country due to its small sample size. In conclusion, healthcare providers gave a marginal level o support to pharmacists as potential immunizers in the country. However, it is recommended to conduct further studies to strengthen the evidence of support from key stakeholders, and identify other potential barriers. It is recommended to conduct studies involving a larger sample size and wider scope of health facilities, including those that will access the pharmacists' willingness to take part in the vaccination practice.
Undergraduate Thesis (BS in Pharmacy)--University of the Philippines Manila, 2015
Keywords: Pharmacists; Healthcare Providers; Immunization